Paper-based biosensors as point-of-care diagnostic devices for the detection of cancers: a review of innovative techniques and clinical applications - Mahmoodpour, Mehrdad; Kiasari, Bahman Abedi; Karimi, Merat; Abroshan, Arezou; Shamshirian, Danial; Hosseinalizadeh, Hamed; Delavari, Alireza; Mirzei, Hamed (Frontiers in Oncology, 2023)
The development and rapid progression of cancer are major social problems. Medical diagnostic techniques and smooth clinical care of cancer are new necessities that must be supported by innovative diagnostic methods and technologies. Current molecular diagnostic tools based on the detection of blood protein markers are the most common tools for cancer diagnosis. Biosensors have already proven to be a cost-effective and accessible diagnostic tool that can be used where conventional laboratory methods are not readily available. Paper-based biosensors offer a new look at the world of analytical techniques by overcoming limitations through the creation of a simple device with significant advantages such as adaptability, biocompatibility, biodegradability, ease of use, large surface-to-volume ratio, and cost-effectiveness. In this review, we covered the characteristics of exosomes and their role in tumor growth and clinical diagnosis, followed by a discussion of various paper-based biosensors for exosome detection, such as dipsticks, lateral flow assays (LFA), and microfluidic paper-based devices (µPADs). We also discussed the various clinical studies on paper-based biosensors for exosome detection.